An investigation of the relationship between metacognitive strategies and vocabulary size in an ESL environment - Engku Ibrahim, Engku Haliza; Isarji, Sarudin; Ainon Jariah, Muhamad; Esa, Zaleha (IACSIT Press, 2013)
Nation (2001) believes that a large amount of vocabulary can be acquired with the help of vocabulary learning strategies and that these strategies prove to be useful for students of different language levels. Studies by Anderson (2002), Rasekh and Ranjbary (2003) and Zhao (2009) indicate agreement as there is positive correlation between vocabulary size and the training of metacognitive strategies of planning, monitoring and evaluation. The purpose of this study therefore was to investigate whether there is relationship between students’ ability to use metacognitive vocabulary learning strategies and their vocabulary level. Participants of this study were 113 Malay English as second language learners (ESL) of a public university in Malaysia studying in an intensive English language programme. A quantitative research method was employed based on a survey questionnaire adapted from Zhao (2009) and the Vocabulary Levels Test by Nation (1990). Findings of this study revealed that there was a weak but negative relationship between the VLT and planning category of the metacognitive awareness (r=-0.113). Based on the Pearson product moment correlation, the relationship was not statistically significant. The findings have beneficial pedagogical implications relevant not only to language instructors but also educators and researchers alike. This paper recommends ways to enhance teachers’ and students’ awareness of the use of the said strategies in acquiring vocabulary more effectively and efficiently.